Gelagat Pengundi di Indonesia: Analisis Rasionaliti Pengundi dalam Memilih Ketua Daerah di Propinsi Riau - Syafhendry (2011)
This research began from idea that behavior of elector took a great attention to be studied by academics, the interest caused by behavior of electors always change their political choice from one general election to other general election, from general election of legislative to general election of regional leader. Moreover, there was a changing of paradigm in Indonesia in general election systems of representative system become direct system. This matter absolutely gives opportunity to political participation of society. This research focus in studying at behavior of elector in event of election of sub province regional leader and town in Riau province. The purpose is to know electors' behavior in decided political choise of regional leader candidate whether it is rational or irrational. This research specified to three sample areas namely Sub- province of lndragiri Hulu, Sub-province of Siak Sri lndrapura and Dumai. Responders came from list of electors which were released by Commission General Election in each Sub-province or town with involved in 466 responders. In this research used questionnaire in collecting data. Meanwhile, the data was analysed descriptively using quantitative and qualitative approach. Relate to west theory which used in analysing the problem of this research, hence, the result proove that behavior of electors at election of regional leader in Riau province is irrational category. this proove quantitatively that electors are more attention to attitude equality of nature figure character, and contiguity of relation became primary factor which reached 54,7 %, comparing with the factor vision of mission, and program is only 45,3 %, in otherhand , this is rational in East, especially in Riau Province because electors focused in reaching goal efficiently and effectively in a normative system. It means the bigger degree of equality between decision of elector belief and the truth in society, it is bigger opportunity that the regional leader candidate will be choosen by them